Prevalence and Correlates of Cognitive Impairment among the Elderly in a General Hospital - Mendes-Chiloff, Cristiane Lara [UNESP]; Torres, Albina Rodrigues [UNESP]; Lima, Maria Cristina Pereira [UNESP]; de Abreu Ramos-Cerqueira, Ana Teresa [UNESP] (Karger, 2009)
Aims: To estimate the prevalence and correlates of cognitive impairment (CI) among the elderly in a general hospital. Methods: A cross-sectional study, including 200 Brazilian inpatients aged 60 years or over, using the Mini Mental State Examination to evaluate CI (dependent variable), and the Geriatric Depression Scale and the Katz and Lawton Index to evaluate basic (BADL) and instrumental activities of daily living (IADL). Results: 56% were women, 29% were dependent for BADL and 77.5% for IADL. The prevalence of CI was 29% and, in the logistic regression, it remained associated with higher age (1 74 years old), number of previous hospitalizations (1 3) and dependency for BADL (being dependent raised the odds of being cognitively impaired). Conclusions: It is essential to train the hospital staff to properly assist these patients, and to orient and support their caregivers. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Early diagnosis; Prevalence studies; Activities of daily living; Cognitive decline; Cognitive impairment; Elderly